Uma análise da produção acadêmica sobre Coordenação Pedagógica, na perspectiva de mestres do Mestrado Profissional em Educação: Formação de Formadores da PUC-SP - Zacarias, Cintia Romero da Silva (2019)
This research had as general objective to identify what about 26 graduates of the Professional Master's Program in Education: Formation of Trainers (Formep) at PUC-SP, discussed about work of the Pedagogical Coordinator in their final assignments, from 2015 to 2017. As a methodological procedure, a documentary analysis (LÜDKE; ANDRÉ, 1986) and stages of the integrative review process were based on the studies of Botelho, Cunha and Macedo (2011). As a theoretical basis, the assignment is based on the concepts of Placco, Almeida and Souza (2011) on the Pedagogical Coordinator. The analysis of all assignments were divided for performance of the Pedagogical Coordinator into two categories: Trainer and Articulator. From these, specifications were revealed in the work of this professional that later allowed to verify the subjects most discussed, the positive and negative aspects in the Pedagogical Coordinator's performance and other gaps will be researched